Therapeutic Potential of Rho Kinase Inhibitors in Corneal Disease: A Systematic Review of Preclinical and Clinical Studies - Laura Andreea Ghenciu; Diana Andrei; Claudia Borza; Roxana Iacob; Emil Robert Stoicescu; Sorin Lucian Bolintineanu; Daniela Iacob; Ovidiu Alin Haţegan (Biomedicines, 2025)
Background/Objectives: Rho-associated coiled-coil-containing protein kinase inhibitors (ROCKis) have now become known as modulators of corneal endothelial wound repair and cell survival. However, evidence remains fragmented across laboratory and clinical reports. We performed a systematic review to synthesize preclinical and clinical data on ROCKis in corneal disease, assess their efficacy and safety, and identify research gaps. Methods: We searched PubMed, Web of Science, Scopus, and Google Scholar (until May 2025) for English-language original studies evaluating ROCKis in corneal models or patients. Inclusion criteria encompassed in vitro, ex vivo, in vivo, and clinical trials reporting functional outcomes (endothelial cell density, wound closure, visual acuity). Results: Thirty-one studies met criteria: 14 preclinical studies and 17 clinical studies. Preclinical models (rabbit, porcine, human explants) uniformly showed ROCKis (Y-27632, Ripasudil, Netarsudil, H-1152) accelerate corneal endothelial cell proliferation, migration, and restoration of a hexagonal monolayer with improved barrier and pump function over days to weeks. In 17 clinical investigations, topical Ripasudil or Netarsudil and cultured cell injections achieved significant corneal thinning, endothelial cell density and central corneal thickness changes, and visual acuity improvements (≥2 lines) with minimal adverse events. Overall bias was moderate in non-randomized studies and low in the RCTs. Conclusions: ROCKis demonstrate consistent pro-regenerative effects on corneal endothelium in multiple models and show promising clinical efficacy in Fuchs endothelial dystrophy and pseudophakic endothelial failure. Future work should explore novel delivery systems and larger controlled trials to optimize dosing, safety, and long-term outcomes.